2016
DOI: 10.4047/jap.2016.8.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dimethyl sulfoxide on bond durability of fiber posts cemented with etch-and-rinse adhesives

Abstract: PURPOSEThis study was undertaken to investigate whether use of an adhesive penetration enhancer, dimethyl sulfoxide (DMSO), improves bond stability of fiber posts to root dentin using two two-step etch-and-rinse resin cements.MATERIALS AND METHODSForty human maxillary central incisor roots were randomly divided into 4 groups after endodontic treatment and post space preparation, based on the fiber post/cement used with and without DMSO pretreatment. Acid-etched root dentin was treated with 5% DMSO aqueous solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…In the present study, the μTBS of EDC and DMSO groups after 10,000 thermal cycles was significantly higher than that in the control group. In line with our findings, Shafiei, Memarpour, and Sarafraz (2016) reported that the application of DMSO significantly increased the bond strength of adhesive-cemented fiber posts in the root canal system after aging. Also, Shafiei, Yousefipour, and Mohammadi-Bassir (2016) reported that application of EDC significantly increased the bond strength of adhesive-cemented fiber posts in the root canal system after aging.…”
Section: Several Macro and Micro Tests Are Available For Assessment Osupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the μTBS of EDC and DMSO groups after 10,000 thermal cycles was significantly higher than that in the control group. In line with our findings, Shafiei, Memarpour, and Sarafraz (2016) reported that the application of DMSO significantly increased the bond strength of adhesive-cemented fiber posts in the root canal system after aging. Also, Shafiei, Yousefipour, and Mohammadi-Bassir (2016) reported that application of EDC significantly increased the bond strength of adhesive-cemented fiber posts in the root canal system after aging.…”
Section: Several Macro and Micro Tests Are Available For Assessment Osupporting
confidence: 92%
“…It seems that the application of DMSO may increase the wetting of collagen and enhance the penetration of adhesive between the collagen fibers exposed by acid etching. Thus, resin impregnation of demineralized dentin can be improved as such (Shafiei, Memarpour, & Sarafraz, 2016).…”
Section: Several Macro and Micro Tests Are Available For Assessment Omentioning
confidence: 99%
“…However, the establishment of effective bonding within the root canal is still a challenge; consequently, debonding of the post and the endodontic lesion has been described as the predominant failure mode of the restoration [ 5 ]. This failure is attributed to intrinsic difficulties in relation to correct handling of adhesive systems in narrow and deep root canal space with limited access and visibility [ 6 ] and high configuration factor (C-factor) within the confined space of root canal [ 7 ] that can even exceed 200. This unfavorable clinical situation results in polymerization shrinkage stress that exceeds cement‒dentin bond strength, causing debonding [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the root canal space was rinsed with EDTA before cementation to eliminate the second thick smear layer and expose the dentinal tubules allowing the SE cement and SE primer to adequately penetrate the radicular dentin (Shafiei, Memarpour et al, 2016). EDTA can adequately disinfect the dentin and allow the dissociation of exposed collagen.…”
Section: Discussionmentioning
confidence: 99%